Liturgical Translation in Europe’s Medieval East: Matters of Civilization and Textual Praxis - Shmiher, Taras (East/West, 2023)
The paper focuses on the medieval period of the history of liturgical translation in Ukraine and Poland. In the ninth century, the evangelizing mission of SS Cyril and Methodius brought Christian translations to the east of what was then Europe. Although religious translations were not cherished in Moravia and Poland, they flourished in Bulgaria, Serbia, and Ukraine. The Roman corpus of liturgical texts existed only in Latin, and socio-political conditions stimulated the emergence of translations from Latin to Polish. The Byzantine corpus was introduced in Old Church Slavonic, which was understood by and accepted among Slavs. Different nations modified these texts according to their local visions and the necessities of their churches. Poland’s and Ukraine’s liturgical praxis under the aegis of the Roman and Byzantine Mother-Churches defined the shaping of different corpora of liturgical books, but the quality of translations was high in all Slavonic translations. The (typically) negatively judged strategy of literalism prepared a foundation for lingual experimentation in semantic expression and helped to spread the local melodies of liturgical tradition. The Church Slavonic language gave a more fruitful impetus to the development of early Ukrainian literature than the Latin language provided to early Polish literature. In fact, the Latin language restrained a similar development of early Polish literature for two centuries.